PARTISIPASI PENYANDANG DISABILITAS DALAM PERENCANAAN PEMBANGUNAN DAERAH DI KOTA TASIKMALAYA - Triana Sapari, Cepi; Asyah, Yesi Nur; Maulana, Irfan (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Public participation is a fundamental principle in the administration of democratic governance, including in regional development planning. However, the participation of vulnerable groups, particularly persons with disabilities, has not been fully guaranteed operationally in local policies. This article aims to analyze the regulation of the participation of persons with disabilities in regional development planning in Tasikmalaya City from the perspective of Government Administrative Law. This study employs a normative juridical method with statutory and conceptual approaches. Legal materials are analyzed using qualitative normative analysis to assess the adequacy and consistency of norms governing the obligations of local governments to ensure the participatory rights of persons with disabilities. The findings indicate that although regional regulations and mayoral regulations have normatively recognized the rights of persons with disabilities, the regulation of their participation in development planning particularly through the Development Planning Deliberation (Musrenbang) remains general and declarative. From the perspective of Government Administrative Law, this condition reflects an operational normative gap that may weaken the protection of participatory rights of persons with disabilities, thereby necessitating the strengthening of more inclusive and equitable local regulations.